High-efficiency blue–green electroluminescence from sublimable cationic iridium(iii) complexes with a pyrazole-type ligand. Issue 12 (4th March 2019) - Zhang, Chen; Ma, Dongxin; Liu, Ruihuan; Duan, Lian
Abstract : High-performance blue and green luminescence is achieved using novel sublimable cationic iridium(iii ) complexes with ppz as the major cyclometalated ligands. Abstract : Sublimable cationic iridium(iii ) complexes achieved by introducing bulky negative counter-ions have shown excellent performance in green-, yellow- and red-emitting devices, revealing their promising future in organic optoelectronic applications. However, the performance of blue-emitting devices remains unsatisfactory. Here, we develop a series of sublimable cationic iridium(iii ) complexes with 1-phenyl-1 H -pyrazole as the major cyclometalated ligand and demonstrate their high thermal stability, and excellent electrochemical and photophysical properties with high photoluminescence quantum yields up to 93%. We also optimize blue–green-emitting OLEDs based on these complexes, achieving a maximum external quantum efficiency of 5.9% with colour coordinates of (0.19, 0.30) and 11.3% with (0.27, 0.50), respectively, among the best performance of blue- and green-emitting devices based on cationic iridium(iii ) complexes.